Atomistic and finite element modeling of mechanical properties and energy dissipation mechanisms in 3D aerosolization-based Voronoi graphene foams - Peng, Weixiang (2025)
Three-dimensional (3D) graphene materials exhibit significant potential for application due to their multifunctional properties, which merge the intrinsic characteristics of 2D graphene with added porosity and unique 3D structural morphologies. In particular, 3D closed-cellular network graphene demonstrates remarkable stiffness while maintaining super-elasticity, outperforming most previously reported carbon-based foams. However, the mechanical properties and energy dissipation mechanisms of these 3D closed-cellular network structures remain poorly understood. To address this, we propose an innovative approach using computational synthesis to construct 3D Voronoi graphene models. Molecular dynamics (MD) and finite element (FE) simulations were then employed to investigate the mechanical properties and microstructure evolution of these 3D Voronoi structures. The results show that the power indices for Young’s modulus, tensile strength, and compressive plateau stress as functions of relative density align closely with the theoretical values for ideal closed-cell foams (1, 1, and 2), indicating that the Voronoi structure exhibits a stretching-dominated deformation behavior. Young’s modulus of the experimental 3D closed-cell graphene precisely follows the fitting function of the continuum model, validating the accuracy of our 3D Voronoi structural morphologies and the significance of our simulation work. Cyclic loading simulations were also conducted to assess the energy absorption and recovery capabilities of 3D graphene. The findings suggest that lower relative densities result in reduced energy dissipation due to less damage at cell boundaries and effective stress relief through bending and folding. In contrast, higher relative densities lead to increased energy dissipation due to higher stress concentrations and associated damage. Overall, this study offers insights into the deformation mechanisms and energy absorption characteristics of 3D Voronoi graphene, enhancing our understanding of the performance and potential applications of 3D graphene.